Respuesta :

Hi there!


To solve, let's rewrite this equation.


[tex]2 (x + 4) - 10 = 12[/tex]


Step 1) Simplify both sides of the equation.


[tex](2) (x) + (2) (4) + - 10 = 12 2x + 8 + - 10 = 12[/tex] (Distribute)


[tex](2x) + (8 + - 10) = 12[/tex] (Combine Like Terms)


[tex]2x + - 2 = 12 2x - 2 = 12[/tex]


Step 2) Add 2 to both sides.


[tex]2x - 2 + 2 = 12 + 2 2x = 14[/tex]


Step 3) Divide both sides by 2.


[tex] \frac{2x}{2} = \frac{14}{2} [/tex]


[tex]x = 7[/tex]


Final Answer -


[tex]x = 7[/tex]


Hope this helps!

Message me if you need anything else, I'd be happy to help you! :D


for solving 1st degree equations (highest exponent on placeholder is 1) the rules are

1. isolate variable
2. divide by coeficient of variable
3. celebrate because you found the answer

remember you can do anything to an equation as long as you do it to both sides


distributive propoerty
a(b+c)=ab+ac

2(x+4)-10=12
distribute the 2 to (x+4)
2(x+4)=2x+8

now we have
2x+8-10=12
add
2x-2=12
add 2 to both sides
2x+2-2=12+2
2x+0=14
2x=14
divide both sides by 2
2/2x=14/2
1x=7
x=7